2008
DOI: 10.1021/la8008199
|View full text |Cite
|
Sign up to set email alerts
|

Polarization Modulation Infrared Reflection−Absorption Spectroscopy Studies of the Influence of Perfluorinated Compounds on the Properties of a Model Biological Membrane

Abstract: A combination of the Langmuir-Blodgett and Langmuir-Schaefer techniques has been used to build a 1,2-dimyristoyl- sn-glycero-3-phosphocholine (DMPC) bilayer at a Au(111) electrode surface with hydrogen-substituted acyl chains in the top leaflet (solution side) and deuterium-substituted acyl chains in the bottom leaflet (gold side). Polarization modulation infrared reflection-absorption spectroscopy was used to determine changes in the conformation and orientation of the acyl chains of DMPC caused by the incorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 34 publications
4
27
0
Order By: Relevance
“…Both PFOA and PFOS resulted in an increase of cell membrane permeability to PI, however, the effect of PFOA 25 mg/L was the strongest. These results are in agreement with previous reports which have found that PFOA and PFOS are able to provoke membrane damage (Nobels et al, 2010), and to alter membrane permeability (Hu et al, 2003;Matyszewska et al, 2007Matyszewska et al, , 2008Matyszewska et al, , 2012Liu et al, 2008;Latała et al, 2009). Kleszczynski and Skladanowski (2009) found that PFOA as other perfluorinated aliphatic acids (PFAs) interacted rapidly with membranes, quickly causing membrane depolarization.…”
Section: Discussionsupporting
confidence: 95%
“…Both PFOA and PFOS resulted in an increase of cell membrane permeability to PI, however, the effect of PFOA 25 mg/L was the strongest. These results are in agreement with previous reports which have found that PFOA and PFOS are able to provoke membrane damage (Nobels et al, 2010), and to alter membrane permeability (Hu et al, 2003;Matyszewska et al, 2007Matyszewska et al, , 2008Matyszewska et al, , 2012Liu et al, 2008;Latała et al, 2009). Kleszczynski and Skladanowski (2009) found that PFOA as other perfluorinated aliphatic acids (PFAs) interacted rapidly with membranes, quickly causing membrane depolarization.…”
Section: Discussionsupporting
confidence: 95%
“…As a consequence of their chemical stability, these compounds exhibit an environmental stability and are transmitted into the mammal food chain [3]. Due to their tendency to bioaccumulate, the compounds affect properties of cell membranes, causing developmental and reproductive disorders [2,4]. It is of particular interest to understand the effect of perfluorinated compounds not only on cellular membranes [5,6], but also on their biomimetic counterparts [7].…”
mentioning
confidence: 99%
“…Several studies have addressed the insertion of perfluorinated compounds into binary model membranes. Oriented mono-and bilayers were investigated by Matyszewska et al using methods including surface pressure and potential measurements, infrared spectroscopy (IR), nuclear magnetic resonance (NMR) techniques, and molecular dynamics (MD) simulations [4,10,11]. While the phospholipid head group tilt against the bilayer normal decreases with rising amounts of inserted perfluorooctanoic acid (PFOA), the lipid acyl chain order increases.…”
mentioning
confidence: 99%
“…1) and transferred onto gold electrodes [19,20]. We showed that perfluorinated compounds may both be incorporated into model membranes during their formation [21] and transfer onto solid support.…”
Section: Introductionmentioning
confidence: 97%
“…Different nature of the changes occurring for different electroactive probes were attributed to electrostatic interactions, which play a very important role in this system. Moreover, PM-IRRAS studies revealed that the presence of these chemicals in DMPC layer induces changes in the orientation and conformation of the acyl chains of DMPC molecules [20]. A decrease in the tilt angles observed when PFCAs were present in the DMPC layers resulted in the increase in membrane fluidity and thickness.…”
Section: Introductionmentioning
confidence: 97%